Rosja i Rosjanie w pamiętnikarstwie polskim od końca XVI do połowy XVII wieku — przegląd tekstów źródłowych - Bauer, Marcin (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
Article enumerates memoirs and diaries written between the late 16th and the middle of the 17th century in which Russian threads occur. As the review of source texts, it acts as an introduction to research on rich and detailed image of Russia and Russians, emerged from many relics of Old Polish memoirism. Paper debriefs also a current studies related to this issue.